Road mapping of artificial intelligence technologies for the food industry: A TDE approach - Zeinab Sarikhani; Khadijeh Mostafaee; Adel Azar (Iranian Journal of Information Processing & Management, 2024)
This paper discusses the application of the technology development envelop (TDE) as a road mapping tool in combination with Delphi method and Analytic Hierarchy Process (AHP). The method aids policy and decision makers in organizations to strategically manage emerging technologies by mapping their anticipated development path. The paper focused on creating a Technology Development Envelope (TDE) for artificial intelligence (AI) technologies in the food industry. At first step a list of AI technologies applicable to the food industry was identified through an expert panel. A hierarchical decision-making model, consisting of 5 criteria and 24 sub-criteria for technology evaluation, was extracted from literature and verified through the Delphi method. The AHP was used to determine the relative importance of criteria and sub-criteria for evaluating the identified technologies. At this step, food safety and social and political acceptance of technology were considered as the most important criteria. Then the expected value of each technology was then calculated over different time periods, resulting in the development of the TDE for AI technologies in the food industry within a ten-year horizon. The analysis of the future indicates that technologies such as computer vision, robotics, industrial automation, and machine learning will undergo improvements over time and eventually transform into dominant technologies in the food industry. These advancements can lead to an increase in quality and efficiency within the food industry. Finally sensitivity analysis was conducted to test the model's sensitivity and explore how policy makers' extreme strategies affects the model's outputs.